2021
DOI: 10.1111/inm.12827
|View full text |Cite
|
Sign up to set email alerts
|

The influence of COVID‐19 on the mental health of final‐year nursing students: comparing the situation before and during the pandemic

Abstract: The COVID‐19 pandemic has had an important impact on the academic world. It is known that university studies can influence the mental health of students, and especially those studying health sciences. In this study, we therefore sought to analyse whether the current pandemic has affected the mental well‐being of final‐year nursing students. This was a multi‐centre study, with a descriptive, longitudinal, and prospective design. Mental well‐being was evaluated using the General Health Questionnaire. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 46 publications
4
50
0
8
Order By: Relevance
“…Kim et al [28] reported that nursing students in MERS situations had higher anxiety scores than adults, and that their anxiety scores were similar to those of firefighters and other frontline medical personnel. Similarly, the lockdown and social distancing measures that were implemented due to COVID-19 had a negative impact on the mental health of nursing students [29,30]. Thus, the majority of nursing students who participated in this study experienced negative emotions (when compared to the other types), which serves as evidence of the current situation and also supports the findings of previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Kim et al [28] reported that nursing students in MERS situations had higher anxiety scores than adults, and that their anxiety scores were similar to those of firefighters and other frontline medical personnel. Similarly, the lockdown and social distancing measures that were implemented due to COVID-19 had a negative impact on the mental health of nursing students [29,30]. Thus, the majority of nursing students who participated in this study experienced negative emotions (when compared to the other types), which serves as evidence of the current situation and also supports the findings of previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…While evidence exists to show a relationship between the COVID-19 pandemic and increase in mental health conditions in students ( Reverte-Villarroya et al., 2021 ) and professional nurses ( Hong et al., 2021 ), it is unclear if mental health was a concern in this study. Mental health did not appear to be a major theme from student responses across the US.…”
Section: Discussionmentioning
confidence: 80%
“…The 18 to 20 age range was found to have higher levels of stress when compared to their older peers. Reverte-Villarroya et al., (2021) compared emotional exhaustion scores between students ( N = 320) experiencing the pandemic and those from a three-year period prior to the pandemic. The researchers discovered a direct association with those students who experienced the pandemic and mental exhaustion scores compared to those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…Fostering of meaning-making processes (“normalization”) in light of the pandemic (i.e., recognition that stress reactions are normal given the current situation) represents a promising approach for psychological intervention ( Castiglioni and Gaj, 2020 ): Promoting the understanding of stressful experiences can be considered as an important coping strategy and can substantially contribute to improving sense of coherence. Complementary pandemic-compatible strategies to improve mental health are already available, such as sports psychology interventions ( Bertollo et al, 2021 ), specific pandemic-related training and preparation ( Reverté-Villarroya et al, 2021 ), and the use of interventions such as mindfulness and a reduction of news consumption ( Aughterson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the specific influence of the COVID-19 pandemic on the perceived locus of control in students are not yet available. For sense of coherence, one previous study in nursing students has shown that it has been significantly less pronounced during the pandemic ( Reverté‐Villarroya et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%